2015
DOI: 10.1039/c5ra12091h
|View full text |Cite
|
Sign up to set email alerts
|

Chemical fractionation of a terrestrial humic acid upon sorption on alumina by high resolution mass spectrometry

Abstract: Using mass spectrometry provided molecular-level insights into the chemical fractionation, and identity of adsorbed compounds, for a terrestrial humic acid rich in condensed aromatics, in alumina-solution systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
5
20
2
Order By: Relevance
“…Fleury et al 26 have also revealed in their investigations using FAs rich in condensed aromatics, that both molecular acidity and hydrophobic character are involved for PACs and low O/C NCAs, and that sorption is the result of surface ligand exchange reactions or hydrophobic interactions according to the atomic O/C ratio of the molecules. Their results compared well with those reported for the sorption of the soluble fraction of an humic acid on alumina, 25 where there was observed a heightened contribution of the hydrophobic interactions due to the highest content in highly condensed aromatic compounds of this terrestrial humic substance. All these ndings imply that sorptive fractionation mechanisms taking place on an alumina surface are similar for HA and FA, with extent of the various mechanisms being largely determined by the amount, nature and reactive ability of the molecules present in HS.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Fleury et al 26 have also revealed in their investigations using FAs rich in condensed aromatics, that both molecular acidity and hydrophobic character are involved for PACs and low O/C NCAs, and that sorption is the result of surface ligand exchange reactions or hydrophobic interactions according to the atomic O/C ratio of the molecules. Their results compared well with those reported for the sorption of the soluble fraction of an humic acid on alumina, 25 where there was observed a heightened contribution of the hydrophobic interactions due to the highest content in highly condensed aromatic compounds of this terrestrial humic substance. All these ndings imply that sorptive fractionation mechanisms taking place on an alumina surface are similar for HA and FA, with extent of the various mechanisms being largely determined by the amount, nature and reactive ability of the molecules present in HS.…”
Section: Introductionsupporting
confidence: 84%
“…Signicance of the existence of such relationships has been widely discussed in our previously published studies. 25,26,63 The numerous homologous series accounting for the large number of different basic structures in PPH, and the wide range of I values observed, complied well with the concept that a FA is made up by small subunits held together by weak forces. It evidenced moreover that surface ligand exchange competed efficiently the cohesion forces of the supramolecular assembly to induce a disruption of the FA structure during the process of sorption.…”
Section: Fa Fractionation Behaviorsupporting
confidence: 71%
See 1 more Smart Citation
“…17,24 It is interesting to note that NOM in natural waters and DOM in soil solutions largely contains hydrophilic fractions including short chain aliphatic carboxylic acids, hydrocarbons and amino acids but few highmolecular-weight, aromatic compounds, and phenolic components. 58 This is highly consistent with the DOM fractions in the supernatant after molecular fractionation by iron oxyhydroxides that we observed in the present study and in aluminum oxides reported by Galindo et al 17,24 Therefore, it is to be expected that the adsorptive fractionation of DOM at hydroxylated mineral surfaces to a great extent determines the chemical components of DOM in labile phases such as surface water and pore water, and a large scale field investigation is needed using ultrahigh resolution mass spectrometry to reveal the molecular composition of labile organic matter in the aquatic and terrestrial environments. In addition, from an environmental perspective, such fractionation led to changes in chemical components of DOM as well as the surface characteristics of the minerals, which will further impact the behaviors of contaminants in the environment such as sorption, transportation and transformation processes.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…20 preferentially removed the most oxidized compounds (O/C ratio >0.4) of DOM, whereas Ca 2+ displayed no preference for distinct molecular fractions. Galindo et al 17,24 published two papers reporting the sorptive fractionation of aquatic fulvic acid (FA) and terrestrial humic acid (HA) on aluminum oxide by ESI-FTMS using a linear ion trap Orbitrap mass spectrometer. They demonstrated that molecule acidity and hydrophobicity were the determining factors that controlled the adsorptive fractionation of FA and HA on aluminum oxide.…”
Section: ■ Introductionmentioning
confidence: 99%